Cerebrovascular and cardiovascular responses to the Valsalva manoeuvre during hyperthermia. - Perry BG; Korad S; Mündel T (John Wiley & Sons Ltd on behalf of Scandinavian Society of Clinical Physiology and Nuclear Medicine, 2023)
BACKGROUND: During hyperthermia, the perturbations in mean arterial blood pressure (MAP) produced by the Valsalva manoeuvre (VM) are more severe. However, whether these more severe VM-induced changes in MAP are translated to the cerebral circulation during hyperthermia is unclear. METHODS: Healthy participants (n = 12, 1 female, mean ± SD: age 24 ± 3 years) completed a 30 mmHg (mouth pressure) VM for 15 s whilst supine during normothermia and mild hyperthermia. Hyperthermia was induced passively using a liquid conditioning garment with core temperature measured via ingested temperature sensor. Middle cerebral artery blood velocity (MCAv) and MAP were recorded continuously during and post-VM. Tieck's autoregulatory index was calculated from the VM responses, with pulsatility index, an index of pulse velocity (pulse time) and mean MCAv (MCAvmean ) also calculated. RESULTS: Passive heating significantly raised core temperature from baseline (37.9 ± 0.2 vs. 37.1 ± 0.1°C at rest, p < 0.01). MAP during phases I through III of the VM was lower during hyperthermia (interaction effect p < 0.01). Although an interaction effect was observed for MCAvmean (p = 0.02), post-hoc differences indicated only phase IIa was lower during hyperthermia (55 ± 12 vs. 49.3 ± 8 cm s- 1 for normothermia and hyperthermia, respectively, p = 0.03). Pulsatility index was increased 1-min post-VM in both conditions (0.71 ± 0.11 vs. 0.76 ± 0.11 for pre- and post-VM during normothermia, respectively, p = 0.02, and 0.86 ± 0.11 vs. 0.99 ± 0.09 for hyperthermia p < 0.01), although for pulse time only main effects of time (p < 0.01), and condition (p < 0.01) were apparent. CONCLUSION: These data indicate that the cerebrovascular response to the VM is largely unchanged by mild hyperthermia.
Keywords: blood pressure; cerebral autoregulation; cerebral blood flow; heat stress; middle cerebral artery blood velocity; Humans; Female; Young Adult; Adult; Valsalva Maneuver; Middle Cerebral Artery; Homeostasis; Cerebrovascular Circulation; Hyperthermia, Induced; Blood Flow Velocity; Blood Pressure